A systematic review of the impact of emergency medical service practitioner experience and exposure to out of hospital cardiac arrest on patient outcomes. - Bray, Janet; Nehme, Ziad; Nguyen, Andrew; Lockey, Andrew; Finn, Judith; Education, Implementation, Teams Task Force of the International Liaison Committee on Resuscitation (2020)
© 2020 Elsevier B.V.